Metastatic colon adenocarcinoma has a significantly elevated expression of IL-10 compared with primary colon adenocarcinoma tumors. Issue 10 (3rd October 2018) - Townsend, Michelle H.; Felsted, Abigail M.; Piccolo, Stephen R.; Robison, Richard A.; O'Neill, Kim L.
ABSTRACT: Classical anti-inflammatory cytokines are known to play a role in both cancer progression as well as cancer elimination. We evaluated the anti-inflammatory cytokines IL-10 and TGF-β in patients with colon adenocarcinoma and metastatic colon adenocarcinoma using immunohistochemical assays to determine the expression of the cytokines between various malignant tissues. We found tissues stained with TGF-β showed no significant upregulation within malignant tumors when compared with normal tissue controls. We observed high levels of TGF-β presence in most tissues similar to GAPDH expression. Within both colon adenocarcinoma and metastatic carcinomas there was a significant variability among patients in the expression of IL-10. While some patients experienced insignificant increases in the cytokine compared with controls, other patients had a clear upregulation of the protein within their tissue. In addition, there was an increase in the number of patients positive for IL-10 upregulation within metastatic tumors when compared with primary tumors. These data indicate that there is substantial variability between patients in regards to IL-10 expression, which may further aid in characterizing tumors and evaluating metastatic potential.